Re-examining the role of benzodiazepines in the treatment of schizophrenia: A systematic review. (February 2015) - Sim, Faye; Sweetman, Isabel; Kapur, Shitij; Patel, Maxine X
Background: Benzodiazepine prescribing for schizophrenia occurs in clinical practice and antipsychotic trials. This review examined the clinical outcomes for benzodiazepines in schizophrenia. Method: A systematic search identified randomised controlled trials that evaluated benzodiazepines in comparison with placebo or antipsychotics, and also as adjuncts to antipsychotics. Relevant clinical outcome data was extracted. Results: Twenty six studies were included with some reporting multiple comparisons. Seven short-term studies compared benzodiazepines with placebo: benzodiazepine superiority was found in two out of five studies for global improvements and two out of four studies for psychiatric/behavioural outcomes. Eleven studies compared benzodiazepines with first-generation antipsychotics (FGAs): four out of nine studies (including two long-term studies) reported greater global improvements for antipsychotics; four out of five studies showed no treatment differences for psychiatric/behavioural outcomes. Fourteen studies compared benzodiazepines (as adjunct to antipsychotics) vs antipsychotics alone (mostly FGAs); benzodiazepine superiority was found for global improvement in one out of eight studies and inferiority in two out of eight short-term studies whereas superiority was found for psychiatric/behavioural outcomes in three out of 12 short-term studies and inferiority in three out of 12 studies. Conclusion: Benzodiazepine superiority over placebo was found for global, psychiatric and behavioural outcomes, but inferiority to antipsychotics on longer-term global outcomes. Conflicting evidence exists regarding the addition of benzodiazepines to antipsychotics; thus the use of benzodiazepines in clinical practice and antipsychotic trials should be limited.